2019
DOI: 10.3390/ijerph16060957
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Maternal Recall to Assess Vaccination Coverage: Evidence from Six Districts in Zhejiang Province, China

Abstract: Background: Although recall-based data are collected by survey when the vaccination records are not available, the preferred estimates remain the record-based ones due to the limited validity of recall-based data. However, the evidence on validity of maternal recalls is limited and varied across vaccine types. To close the gaps, we validated the maternal recall on vaccination against record-based data in six districts in Zhejiang Province, China. Methods: We used a cross-sectional survey of about 648 household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
3
11
1
Order By: Relevance
“…Hu et al compared survey data and administrative data in children’s vaccination, to evaluate the impact of recall bias by their mother. The results showed the frequency of over-reporting of vaccination in the survey data, up to 6.6% for DPT vaccine, linked to social desirability bias 43 .…”
Section: Discussionmentioning
confidence: 96%
“…Hu et al compared survey data and administrative data in children’s vaccination, to evaluate the impact of recall bias by their mother. The results showed the frequency of over-reporting of vaccination in the survey data, up to 6.6% for DPT vaccine, linked to social desirability bias 43 .…”
Section: Discussionmentioning
confidence: 96%
“…Agreement between the observed prevalence of exclusive breastfeeding at 3 months postpartum, and a 12‐month postpartum survey that asked about the prevalence of breastfeeding practices at 3 months postpartum was also found to be high (Schneider et al, 2020). Finally, Hu et al (2019) found >90% agreement between clinical records of vaccinations given to children in the previous year and maternal recall. These studies comparing direct observation with recall across several different timeframes report variable validity depending on the intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, recall and social-desirability biases in relation to routine vaccination of the child could distort the findings. On the other hand, previous studies found that the history of child vaccination was accurately identified through maternal recall and concluded that it might be used to estimate the vaccination coverage ( Binyaruka & Borghi, 2018 ; Hu et al, 2019 ). The complete anonymity of this study decreases the possibility of a social-desirability bias ( Lelkes et al, 2012 ).…”
Section: Limitationsmentioning
confidence: 99%